Manajemen Program Kegiatan Ekstrakurikuler Bahasa Inggris di SMK Bisnis dan Teknologi - Iwan Budiarso; Tjipto Djuhartono; Saidatun Nafisah (Pascasarjana IAI Nasional Laa Roiba Bogor, 2025)
Extracurricular activities are as additional activities for students outside the classroom and outside of study hours. The purpose of extracurricular activities is to develop independent interests, talents, and personalities for students. The form of extracurricular activity program that can be applied in schools is English extracurriculars. This extracurricular explores and develops the potential of English language skills. There are at least 5 extracurricular benefits of English for students, namely, improved English skills, increased self-confidence, practicing public speaking skills, learning English with fun methods, and better future job opportunities. The implementation of an optimal English extracurricular activity program is a very essential provision for students in facing the world of work in the future, especially for vocational high school (SMK) students whose graduates are ready to work. The English extracurricular activity program needs to be designed to deepen and hone students' four English skills, namely listening, speaking, reading, and writing. However, in its implementation, the English extracurricular activity program is faced with various problems or challenges that require special and serious handling in the management process. The purpose of the study is to identify and analyze English extracurricular management in SMK Business and Technology, how schools make policies in planning, implementing, controlling, evaluating, and recognizing driving and inhibiting factors. The research method uses qualitative descriptive by determining informants consisting of school principals, teachers or extracurricular instructors by conducting observations, interviews, and documentation studies. The results and discussions, SMK Business and Technology has carried out planning, implementation, control, evaluation well and has known the driving and inhibiting factors. However, there are still some notes and suggestions.